Educational Modernity: Representation and Writings - Magalhães, Justino (2016)
The set of texts published in this issue focus, to varying degrees, on the education-institution as a singularity, as an institution-school, or, in a narrower sense, as institutional schooling. From a more objective perspective, they focus on the school. Within the scope of the theme and its timeframe, the concept of representation provides a plurality of objects, figurations, meanings and forms of communication and appropriation. Representation encompasses both the uniform and the diverse, reordering the historical and pedagogical fabric, language, symbology, theoretical and conceptual framework, intentionality and the nature of the object. In other words, it changes authorship and the ways of symbolising and relating.